1972
DOI: 10.1172/jci106806
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Pancreas in Vitamin B12 Absorption: Studies of Vitamin B12 Absorption in Partially Pancreatectomized Rats

Abstract: A iB S T R A C T The effect of partial pancreatectomy(80-90%,) on vitamin Bn absorption was studied in the rat. The absorption of 5 ng of^'Co-labeled vitamin B1u was significantly reduced from 70 ±2.5% (mean +SE) in control and sham-operated rats to 32 ±2.6% in partially pancreatectomized rats. Hog pancreatic extract (0.17 g/kg) improved vitamin B12 absorption from 30.0 to 61.0% in partially pancreatectomized rats but did not alter vitamin B,2 absorption in control rats. Chloramphenicol did not enhance vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1973
1973
1991
1991

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…This consideration is important since it suggests that under physiological in vivo conditions, IF-Bi2 binding to ileal IF-Br2-binding sites might be different from that observed with homogeneous IF isolated from gastric juice and gastric mucosa. Other recent studies (34)(35)(36), demonstrating B12 malabsorption in humans and rats with pancreatic insufficiency and its correction with pancreatic extracts and highly purified preparations of trypsin, suggest that differences might exist between in vivo and in vitro ileal IF-B,2 binding.…”
Section: Methodsmentioning
confidence: 96%
“…This consideration is important since it suggests that under physiological in vivo conditions, IF-Bi2 binding to ileal IF-Br2-binding sites might be different from that observed with homogeneous IF isolated from gastric juice and gastric mucosa. Other recent studies (34)(35)(36), demonstrating B12 malabsorption in humans and rats with pancreatic insufficiency and its correction with pancreatic extracts and highly purified preparations of trypsin, suggest that differences might exist between in vivo and in vitro ileal IF-B,2 binding.…”
Section: Methodsmentioning
confidence: 96%
“…Studies in partially pancreatectomized rats (9) have shown that ileal receptors for IF-Cbl are present in normal amounts and that they function normally in terms of binding the IF-Cbl complex. Cbl malabsorption in humans with pancreatic insufficiency is not corrected by the oral administration of antibiotics nor is it corrected by binding Cbl to human gastric juice or crude hog IF in vitro and then administering it either orally or in the latter case directly into the distal ileum (3).…”
mentioning
confidence: 99%
“…Vitamin B,, absorption studies in rats. Partial pancreatectomies were performed on male albino rats2 as described by Scow (6) and modified by Toskes and Deren (4).' After a suitable recovery period, 1 ml of '7Co-labeled vitamin B,2 containing 5 ng of vitamin B12 (13-15 ,uCi/,ug) was administered via gastric tube to fasted rats.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin B12 malabsorption occurs in some patients with chronic pancreatic exocrine insufficiency (1)(2)(3) and in rats subjected to partial pancreatectomy (4). Although hog pancreatic extract corrects the absorptive defect in both humans and animals (1,2,4), the precise constituent in the pancreatic extract responsible for the enhancement of vitamin B12 absorption has not been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation